2005
DOI: 10.1073/pnas.0508489102
|View full text |Cite
|
Sign up to set email alerts
|

The architecture of pre-mRNAs affects mechanisms of splice-site pairing

Abstract: The exon͞intron architecture of genes determines whether components of the spliceosome recognize splice sites across the intron or across the exon. Using in vitro splicing assays, we demonstrate that splice-site recognition across introns ceases when intron size is between 200 and 250 nucleotides. Beyond this threshold, splice sites are recognized across the exon. Splice-site recognition across the intron is significantly more efficient than splice-site recognition across the exon, resulting in enhanced inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
271
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(290 citation statements)
references
References 33 publications
18
271
1
Order By: Relevance
“…Drosophila represented an interesting case, with slightly higher levels of exon skipping than intron retention detected, despite the predominant intron definition signature observed in splicing network analysis of constitutive introns. This observation suggests that intron definition may be favored in constitutively spliced Drosophila transcripts, with AS more common in situations involving exon definition, consistent with the long intron lengths associated with many known AS events in this organism (25).…”
Section: Widespread Constraints On Splicing Element Evolution Associatedsupporting
confidence: 64%
See 2 more Smart Citations
“…Drosophila represented an interesting case, with slightly higher levels of exon skipping than intron retention detected, despite the predominant intron definition signature observed in splicing network analysis of constitutive introns. This observation suggests that intron definition may be favored in constitutively spliced Drosophila transcripts, with AS more common in situations involving exon definition, consistent with the long intron lengths associated with many known AS events in this organism (25).…”
Section: Widespread Constraints On Splicing Element Evolution Associatedsupporting
confidence: 64%
“…27). In both the fishes and the flies, splice site strength changed in a correlated fashion with intron length, suggesting that shorter intron lengths increase splicing efficiency in both of these systems (25).…”
Section: Widespread Constraints On Splicing Element Evolution Associatedmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been previously shown that the efficiency of splicing in NE drops sharply when intron length exceeds 200 nt (Fox-Walsh et al 2005). Consequently, we investigated whether splicing of long introns is enhanced by RNAP II transcription.…”
Section: Splicing Of Long Introns Is Equivalent In Synthetic and Rnapmentioning
confidence: 99%
“…Intron and exon lengths reflect the constraints imposed by splicing recognition and frequency of AS [18]. Introns flanking alternatively spliced exons are long, whereas constitutively spliced exons are flanked by short introns [60]. Also, enlarged exons lead to exon skipping, but if the flanking introns are short, the enlarged exon is included [61].…”
Section: Features Of Exons and Intronsmentioning
confidence: 99%